Nutrition Promotion Provision of Balanced Nutritious Food to Optimize the Nutritional Status of Harapan Bunda Kindergarten Students, Muaro Jambi Regency - Perdana, Silvia Mawarti; Kusmawan, David; Wulansari, Arnati; Asparian, Asparian; Hidayat, Ahmad Thohir (Abdi Masyarakat, 2024)
Optimal children’s nutritional status is an indicator of achieving child growth according to their age. Optimizing nutritional status is supported by providing nutrition intake to meet children's daily nutrition needs. Kindergarten students need  nutritionally, healthy and safe food. Providing balanced nutritious food supplies for kindergarten students requires knowledge, attitudes and good practices from parents, as well as implementation of nutritionally balanced meal that are integrated into the kindergarten learning curriculum from the school. Harapan Bunda Kindergarten, which is located in Talang Belido Village, Sungai Gelam District, Muaro Jambi Regency, has never received nutrition promotion regarding the nutritious food for kindergarten students. The food supplies for kindergarten students brought by their parents also do not implement balanced diet. This community service activity aimed to organize nutritional promotion of balanced nutritious food to optimize the nutritional status of kindergarten students with the targets are teachers and parents. The results of community service activities showed that there is an increase in target’s knowledge before and after being given education which is not significantly different (Sig.>0.05). It is necessary to get used to implementing balance diet on children's meal which contain carbohydrate foods, protein foods, vegetables, fruit, and drinking water consumption (1200-1500 ml per day)..